Pre–post evaluation of effects of a titanium dioxide coating on environmental contamination of an intensive care unit: the TITANIC study. Issue 3 (July 2018) - de Jong, B.; Meeder, A.M.; Koekkoek, K.W.A.C.; Schouten, M.A.; Westers, P.; van Zanten, A.R.H.
Summary: Background: Among patients admitted to European hospitals or intensive care units (ICUs), 5.7% and 19.5% will encounter healthcare-associated infections (HAIs), respectively, and antimicrobial resistance is emerging. As hospital surfaces are contaminated with potentially pathogenic bacteria, environmental cleanliness is an essential aspect to reduce HAIs. Aim: To address the efficacy of a titanium dioxide coating in reducing the microbial colonization of environmental surfaces in an ICU. Methods: A prospective, controlled, single-centre pilot study was conducted to examine the effect of a titanium dioxide coating on the microbial colonization of surfaces in an ICU. During the pre- and post-intervention periods, surfaces were cultured with agar contact plates (BBL RODAC plates). Factors that were potentially influencing the bacterial colonization of surfaces were recorded. A repeated measurements analysis within a hierarchic multi-level framework was used to analyse the effect of the intervention, controlling for the explanatory variables. Findings: The mean ratio for the total number of colony-forming units (cfus) in a room between the pre- and post-intervention periods was 0.86 (standard deviation 0.57). The optimal model included the following explanatory variables: intervention ( P =0.065), week ( P =0.002), culture surfaces ( P <0.001), ICU room ( P =0.039), and interaction between intervention and week ( P =0.002) and between week and culture surfaces ( P =0.031). The effect of the intervention on the number of cfus from all culture plates in Week 4 between the pre- and post-intervention periods was -0.47 (95% confidence interval -0.24 to - 0.70). Conclusion: This study found that a titanium dioxide coating had no effect on the microbial colonization of surfaces in an ICU.